THE IMPLEMENTATION OF SOCIAL SUFISM IN PHILANTHROPIC PRACTICES: THE UTILIZATION OF ZAKAT AND INFAQ DURING THE COLONIAL PERIOD - Muhammad Ikhsan Ghofur; Pasya Komala Hizriastuti; Tatik Khalifah (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study examines the implementation of social Sufism in the practice of Islamic philanthropy during the colonial period in Indonesia. The background of this research lies in the socio-religious condition of Muslim communities under colonial rule, which continued to demonstrate solidarity, compassion, and independence through philanthropic practices rooted in Sufi spiritual values. The aim of this study is to understand how the teachings of social Sufism influenced Islamic philanthropic behavior oriented toward communal welfare. This research employs a qualitative approach using library research methods, with data collected from classical and modern literature relevant to social Sufism and Islamic philanthropy. The data were analyzed through content analysis to interpret the connection between Sufi teachings and philanthropic practices within the socio-historical context of colonialism. The findings reveal that values such as sincerity (ikhlas), asceticism (zuhd), contentment (qana’ah), trust in God (tawakkal), and perseverance (mujahadah) served as moral foundations for Islamic social movements through organizations such as Sarekat Islam, Muhammadiyah, Nahdlatul Ulama, and Al-Irsyad. These movements strengthened community solidarity and established various social, educational, and economic institutions that alleviated suffering under colonial oppression. In conclusion, social Sufism functioned as a spiritual force integrating personal piety with social action, significantly contributing to the development of Muslim social welfare during the colonial era